2021
DOI: 10.1093/mnras/stab2696
|View full text |Cite
|
Sign up to set email alerts
|

The mean free path of ionizing photons at 5 < z < 6: evidence for rapid evolution near reionization

Abstract: The mean free path of ionizing photons, λmfp, is a key factor in the photoionization of the intergalactic medium (IGM). At z ≳ 5, however, λmfp may be short enough that measurements towards QSOs are biased by the QSO proximity effect. We present new direct measurements of λmfp that address this bias and extend up to z ∼ 6 for the first time. Our measurements at z ∼ 5 are based on data from the Giant Gemini GMOS survey and new Keck LRIS observations of low-luminosity QSOs. At z ∼ 6 we use QSO spectra from Keck … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
76
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(92 citation statements)
references
References 82 publications
8
76
0
Order By: Relevance
“…Indeed, models assuming star forming galaxies as main contributors to the UV background show that (relatively faint) galaxies tend to start the reionization process too early (Naidu et al 2020). It is also worth noting that UV selected star forming galaxies do not show an abrupt drop in their UV luminosity density at z ∼ 5.5, where the bulk of the reionization event is taking place, but they show an accelerated evolution only at z ∼ 8 − 9 (Oesch et al 2018;Bouwens et al 2021), too early to be in agreement with the redshift evolution shown by the MFP measured by Becker et al (2021) and by the photo-ionization rate (Calverley et al 2011;Wyithe & Bolton 2011;Davies et al 2018).…”
Section: Introductionsupporting
confidence: 58%
See 1 more Smart Citation
“…Indeed, models assuming star forming galaxies as main contributors to the UV background show that (relatively faint) galaxies tend to start the reionization process too early (Naidu et al 2020). It is also worth noting that UV selected star forming galaxies do not show an abrupt drop in their UV luminosity density at z ∼ 5.5, where the bulk of the reionization event is taking place, but they show an accelerated evolution only at z ∼ 8 − 9 (Oesch et al 2018;Bouwens et al 2021), too early to be in agreement with the redshift evolution shown by the MFP measured by Becker et al (2021) and by the photo-ionization rate (Calverley et al 2011;Wyithe & Bolton 2011;Davies et al 2018).…”
Section: Introductionsupporting
confidence: 58%
“…The strong redshift evolution of the mean free path (MFP) of ionizing photons into the intergalactic medium (IGM), which appears to decrease significantly in the redshift interval 4 < z < 6, could be indicative of a rapid change in the ionization level of the IGM since, for a given source emissivity, the photo-ionization rate Γ HI is simply proportional to the MFP. Indeed a fast drop of the MFP at z ∼ 6 has been recently derived by Becker et al (2021) with respect to the extrapolation from values measured at lower redshifts (Worseck et al 2014).…”
Section: Introductionmentioning
confidence: 73%
“…Many putative detections at higher redshifts (z ∼ 3) over the next 10 yr turned out to be non-LyC contamination from lower-redshift interlopers at small angular separation (e.g., Vanzella et al 2012;Mostardi et al 2015;Siana et al 2015). Another difficulty stems from IGM attenuation at higher redshifts, which (i) makes LyC measurements at or beyond reionization (z  6) impossible because all of the LyC photons are absorbed (e.g., Becker et al 2021); and (ii) makes imaging detections of the LyC at moderately high redshifts (z = 2-3) complicated because the Lyman series and LyC attenuation are uncertain along any particular line of sight (e.g., Inoue et al 2014;Steidel et al 2018). Moreover, the LyC is too faint at z  4 to be detected with even the largest contemporary ground-based telescopes.…”
Section: Introductionmentioning
confidence: 99%
“…Observational studies of the reionization of the intergalactic medium (IGM) have predominantly focused on the end of this process. Quasar absorption spectra (e.g., Fan et al 2006;McGreer et al 2015) show that reionization was largely finished by z ∼ 6 (perhaps some small neutral patches remain to z ∼ 5.5; e.g., Becker et al 2015Becker et al , 2021. How fast reionization proceeds, what drives it, and how and when it began are poorly constrained.…”
Section: Introductionmentioning
confidence: 99%